Hölderlin als Denkmal in der Kunst des 19. und 20. Jahrhunderts - Loos, Helmut (Muzikološki zbornik, 2011)
Although we attribute to Hölderlin poetry very substantial musical qualities it is a fact that he wasn't a reference poet for the Romantic Lied. Already his contemporary composers such as Ludwig van Beethoven didn't consider him to be significant. An exception between them is Robert Schumann that was completely fascinated by Hölderlin poetry already in his youth.
Keywords: Beethoven, Ludwig von, 1770-1827; Hölderlin, Johann Christian Friedrich, 1770-1843; romantic lied; romantični samospev; Schumann, Robert, 1810-1856